Contaminated Fungi in the Biology Department laboratories and Antagonistic Potentiality of Myrtrus Communis Volatile oil Against the Isolated Fungi - Najem, Ali Muayyed (Al-Nahrain Journal of Science, 2018)
Antagonistic activity of Myrtrus communis volatile oil was evaluated against fungi isolated and detected in different hoods in Biology Department in order to eliminate and purge the hoods of laboratories from contaminant fungi which are rendered scientific projects. Many fungi samples were detected in four laboratories which were Aspergillus fumigates, Asp.niger, Asp.flavus, Cryptococcus albidus, Fusarium solani, Asp.terrus, Asp.terriola, Penicillium notatum and Mucor sp. Only four pure isolates were gained due to difficulties in purification of the isolates included Fusarium solani, Asp.fumigatus, Asp.niger and Asp.Flavus. Volatile oil of Myrtrus communis showed the highest fungicidal effect causing 100 % inhibition against Asp.fumigates and the lowest was against Fusarium solani.